Maternotoxicity and fetotoxicity in Rattus norvegicus albinus exposed to tramadol during the late phase of pregnancy. Issue 19 (22nd September 2021) - Akhtar, Muhammad Furqan; Younas, Sobia; Saleem, Ammara; Baig, Mirza Muhammad Faran Ashraf; Sharif, Ali; Abdel‐Daim, Mohamed M.; Rasul, Azhar; Saleem, Mohammad
Abstract: Objectives: Tramadol, an atypical opioid, is clinically efficacious in treating moderate to severe pain. The aim of current study was to find out the toxicological effects of tramadol exposure to pregnant rats and fetuses during the late phase of pregnancy. Methods: Wistar pregnant rats were exposed to 1.25, 2.5, or 5 mg/kg/day tramadol from 14th to 20th day of pregnancy. The same therapy was given to nonpregnant rats for 7 days. The body weight, oral glucose and lipid tolerance tests, and effect on complete blood parameters in both pregnant and nonpregnant rats were determined. On 20th day, maternal placentas were excised and weighed while fetuses were observed for any deformity and growth retardation. Oxidative stress biomarkers were estimated in the liver and kidney tissue homogenates of the pregnant and nonpregnant rats while the whole fetus homogenate was processed for the same. Moreover, histopathology of the liver and kidney of pregnant and nonpregnant rats were carried out. Results: Tramadol administration did not significantly alter the area under curve of the blood glucose and triglyceride levels in both the pregnant and nonpregnant rats. It reduced the live fetuses, placental weights, fetal length, and fetal weights. Tramadol treated pregnant rats showed significantly ( p  < .05) reduced red blood cells, hematocrit, hemoglobin, and platelets with reference to control group. Similarly, structural abnormalities and malfunctioning of the liver and kidney of pregnant rats were instituted; however, it did not affect the structural integrity of nonpregnant rats. A substantial ( p  < .001–.0001) altered glutathione and malondialdehyde levels in the fetuses, pregnant, and nonpregnant animals (tissue homogenates) at all dosage levels were indicative of tramadol induced oxidative stress. Furthermore, tramadol exposure resulted in more significant ( p  < .01–.001) alteration of lipid profile in the pregnant than the nonpregnant animals. Conclusion: Acquired results suggested the maternotoxic and fetotoxic effects of tramadol exposure during the late gestation period.